The Effectiveness of Similarities Integration in Learning Course (5E’s) on The Achievement of Scientific Concepts by Sixth Grade School Girls in Riyadh City. - al - Zahrani, Wafa bint Ashour (Journal of Educational and Psychological Sciences, 2018)
This study aims to identify the effectiveness of similarities integration in learning course (5E’s) on the achievement of scientific concepts by sixth grade school girls in Riyadh city. To achieve the study objectives, the researcher used the experimental approach of quasi-experimental design based on pre and post design of (experimental and control) group. The researcher prepared achievement test as study tool according to mental processes levels in The Trends in International Mathematics and Science Study (TIMSS), these levels are (Knowledge- Application- Inference). Study population includes all school girls of sixth grade of public schools in Riyadh, concluded in the first semester for the academic year 2017/2018, totaling (32219) girls. The researcher selected a random sample of (64) female students divided into two groups: 32 girls for the experimental group and 32 girls of the control group. The study results revealed the existence of a significant difference at (α≤0.05) between means average of girls of the experimental group who studied through the integration of similarities in learning course (5E’s), in the post application of achievement test at (Knowledge, Application, Inference) levels, whereas their total average was (19.03) out of (30.00), compared to means average of girls of the control group which was (13.97), who studied through the traditional method, such difference was in favor of the experimental group. According to Eta-squared (h2), the degree of effectiveness was (0.45), indicating the existence of significant efficacy, attributed to the use of integration of similarities in Learning Course (5E’s) on the achievement of scientific concepts by study sample members. In view of these results, the researcher provided a set of recommendations and suggestions for the integration of similarities strategy in learning course.